ANALYSIS OF MOTIVATION PHASE OF THE HAPA THEORY (HEALTH ACTION PROCESS APPROACH) AND INTENTION TO EXCLUSIVE BREASTFEEDING IN THE SIDOSERMO PRIMARY HEALTHCARE CENTER, SURABAYA - Anak Agung Sriska Prasnantiawardani; Shrimarti Rukmini Devy (Universitas Airlangga, 2021)
ABSTRACTExclusive breastfeeding can encourage optimal growth and development, especially during the child’s critical period which spans from when the baby is born until 2 years old. The objective of this study was to analyze the motivational phase of the Health Action Process Approach (HAPA) theory with the intention of exclusive breastfeeding in the work area of the Sidosermo Primary Healthcare Center. This study was a quantitative cross-sectional study with an observational research design. The sampling technique was conducted through the systematic random sampling technique with a total sample of 32 people. The study showed that risk perception has a significant influence on the intention of exclusive breastfeeding with a significance value of 0.014 < α (0.05) and an odds ratio of 0.101. This suggests that respondents who had the right perception about exclusive breastfeeding are 0.101 times more likely to exclusively breasfeed their child than respondents who had a wrong perception. This study also showed that there was a significant influence between self-efficacy towards the intention of exclusive breastfeeding, with a significance value of 0.006 < α (0.05). Respondents who felt that they were able to give exclusive breastfeeding were 17 times more likely to provide exclusive breastfeed than those who felt they were less able. The results of this study indicated that there was an influence between the outcome expectancies with the intention of exclusive breastfeeding with a significance value of 0.004 < α (0.05) and an odds ratio of 28.8. It means that respondents who had high expectations had 28.8 times more intention to provide exclusive breastfeeding than respondents who had low expectations. Keywords: exclusive breastfeeding, intention, Health Action Process Approach (HAPA)